TECHNOLOGICAL ASPECTS OF DESIGN OF EDUCATIONAL PROGRAMS OF PREPARATION OF THE APPLIED BACHELOR - Tatyana P. Petukhova (Высшее образование в России, 2016)
This article focuses on the technological aspects of creation of bachelor’s educational programs providing assignment to graduates qualification « an applied bachelor».The basis of this technology is the modular principle of content formation and a cluster modelof interaction with potential employers.